Atrioventricular mechanical coupling and major adverse cardiac events in female patients following acute ST elevation myocardial infarction. (15th January 2020) - Backhaus, Sören J.; Kowallick, Johannes T.; Stiermaier, Thomas; Lange, Torben; Koschalka, Alexander; Navarra, Jenny-Lou; Uhlig, Johannes; Lotz, Joachim; Kutty, Shelby; Bigalke, Boris; Gutberlet, Matthias; Hasenfuß, Gerd; et al.
ABSTRACT: Background: Sex-specific outcome data following myocardial infarction (MI) are inconclusive with some evidence suggesting association of female sex and increased major adverse cardiac events (MACE). Since mechanistic principles remain elusive, we aimed to quantify the underlying phenotype using cardiovascular magnetic resonance (CMR) quantitative deformation imaging and tissue characterisation. Methods: In total, 795 ST-elevation MI patients underwent post-interventional CMR imaging. Feature-tracking (CMR-FT) was performed in a blinded core-laboratory. Left ventricular function was quantified using ejection fraction (LVEF) and global longitudinal/circumferential/radial strains (GLS/GCS/GRS). Left atrial function was assessed by reservoir (εs), conduit (εe) and booster-pump strains (εa). Tissue characterisation included infarct size, microvascular obstruction and area at risk. Primary endpoint was the occurrence of MACE within 1 year. Results: Female sex was associated with increased MACE (HR 1.96, 95% CI 1.13–3.42, p  = 0.017) but not independently of baseline confounders ( p  = 0.526) with women being older, more often diabetic and hypertensive ( p  < 0.001) and of higher Killip-class ( p  = 0.010). Tissue characterisation was similar between sexes. Women showed impaired atrial (εs p  = 0.011, εe p  < 0.001) but increased systolic ventricular mechanics (GLS p  = 0.001, LVEF p  = 0.048). While atrial and ventricular function predicted MACE in men only LV GLS and GCS were associated with MACE in women irrespective of confounders (GLS p  = 0.036, GCS p  = 0.04). Conclusion: In men ventricular systolic contractility is impaired and volume assessments precisely stratify elevated risks. In contrast, women experience reduced atrial but increased ventricular systolic strain. This may reflect ventricular diastolic failure with systolic compensation, which is independently associated with MACE adding incremental value to sex-specific prognosis evaluation. Highlights: Atrial function is reduced in women after AMI, while ventricular systolic function is increased. In women, ventricular systolic compensation is independently associated with MACE. In women, deformation assessments but not volumetric analyses identify elevated risks.